Cryptotanshinone targets tumor-immune-microbiome axis to suppress colorectal cancer - Yang, Zhenya; Zhou, Mengting; Luo, Fenglin; Feng, Shiqi; Tan, Yu; Wang, Qiqian; Cheng, Zeneng; Tan, Ruirong; Li, Rui (Frontiers in Pharmacology, 2025)
BackgroundColorectal cancer (CRC) progression involves complex interactions between tumor cells, immune evasion, and metabolic reprogramming. Cryptotanshinone (CTS), a bioactive diterpenoid from Salvia miltiorrhiza, has demonstrated anticancer potential, but its integrated effects on CRC remain unclear.MethodsWe employed both in vitro and in vivo models to evaluate the therapeutic effects and mechanism of CTS. Using MC38 cells and mouse-derived CRC organoids, we assessed its impact on proliferation and apoptosis through CCK-8, clonogenic, and Annexin V/PI assays. For vivo evaluation, a murine AOM/DSS-induced CRC model was established and administered CTS via intraperitoneal injection for 8 weeks. Comprehensive analyses included histopathology, immune profiling by flow cytometry, 16S rRNA sequencing of gut microbiota, and LC-MS-based metabolomics.ResultsCTS exerted potent anti-CRC effects, suppressing tumor cell proliferation and inducing apoptosis in vitro. In AOM/DSS-induced mice, CTS significantly inhibited tumor growth, ameliorated colon shortening and pathological damage, and reduced inflammation. Mechanistically, CTS alleviated T cell exhaustion, reversed metabolic dysregulation, and restored gut microbiota community structure.ConclusionCTS effectively suppresses CRC progression. Its efficacy is associated with the coordinated modulation of the tumor-immune-microbiome axis, involving direct cytotoxicity, reduced PD-1+ T cell levels, and restructuring of the gut microbial community. These results highlight CTS as a promising multi-faceted therapeutic candidate and provide a preclinical rationale for its further development.